The Effect of the Project-Based Learning (PjBL) Model on Students’ Learning Motivation in the Topic of the Periodic Table of Elements - Irawan, Arfa Destira; Okmarisa, Heppy (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This research is motivated by the lack of student learning motivation at MAN 4 Kampar. This is caused by students having difficulty understanding abstract material as well as the use of learning models that are less varied. The aim of this research is to find out the effect of the Project Based Learning (PJBL) model on student learning motivation in the subject of the periodic table of elements. This research was conducted in the odd semester of the 2025/2026 academic year at MAN 4 Kampar. This study uses a quasi-experimental research type with a pretest-posttest Non-Equivalent Control Group Design. The sample in this study consisted of two classes, namely class X.a as the experimental class and class X.b as the control class. The instruments used were in the form of student motivation observation sheets and student motivation questionnaires. The results of this study showed that in the experimental class using the learning model Project-based learning (PJBL) can boost motivation based on T-test results, which showed a significance value of <0.001, smaller than 0.05. The conclusion of this study is that the Project Based Learning model affects students’ motivation to learn the periodic table material.